Law Enforcement of Illegal Parking Fees at Alfamart and Indomaret Stores in Indonesia - Rizka, Nanda Dwi; Ilhamdi, Ilhamdi; Novianty, Rica Regina; Putri, Tania Dwika; Lubis, Arief Fahmi (Riwayat: Educational Journal of History and Humanities, 2024)
This study is a qualitative study with a descriptive approach. The data used in this article are primary data that researchers obtain from various credible sources such as books, scientific journals, magazines, and a number of other sources that are commonly used in each study. The analysis techniques used in this article are data collection, data reduction, data selection, and drawing conclusions